Análise ergonômica do trabalho docente na pós-graduação: estudo de caso no departamento de engenharia de produção de uma instituição de ensino superior (IES) pública federal - Vieira, Marina Helena Pereira (Universidade Federal de São Carlos, 2018)
The aim of this research is to analyze the work activity of higher level teaching, identifying the constraints that the professionals of this category are submitted, due - especially - to the system of evaluation of the intellectual production linked to the postgraduate programs. It will be studied the teacher’s activities that works in the Department of Production Engineering (PE) of a federal public university, in the interior of the state of São Paulo. The choice of this theme considers that the teaching work started to have a new logic in the academic routines, based on the acceleration and intensification of activities and the stimulus to productivity, that reproduces in the university scope the characteristics of flexible work. Thus, the teaching activity, related to teaching, research and extension, as well as the administrative management of the university, will be analyzed from the perspective of the Activity Ergonomics. As for the methodological design, this research is classified as descriptive, with a qualitative approach, of a bibliographic character, complemented by the application of a single case study, outlined by the methodological approach of the Ergonomic Work Analysis (EWA), which allows to systematize the investigation of situation of the work environment. he results show that the teachers who work in the postgraduate program of the selected institution are submitted to greater constraints and experience feelings of frustration due to the charges for publication. Some teachers consider the evaluation of intellectual production as an oppressive and motivating process of unproductive productivism, which does not reflect the performance of a good teacher in the exercise of his teaching, research and extension activities. Despite the physical and cognitive impairments arising from the function, the work environment, the autonomy to perform the activities and the satisfaction in developing research are factors that positively influence the work activity of this labor category. Therefore, higher level teaching has proved to be an activity of high physical and cognitive demand and represents an even more pronounced dichotomy in graduate studies, between the pleasures of producing knowledge and the wear and tear that the demands of intellectual production impose.
Ergonomic Work Analysis of postgraduate teaching: case study in the production engineering department of a federal public university
Keywords: Análise Ergonômica do Trabalho; Pós-graduação; Trabalho Docente; Ergonomic Work Analysis; Post-graduation; Teaching Work; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::ERGONOMIA; ENGENHARIAS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL::ANALISE INSTITUCIONAL